Experimental investigation on gas turbine engine performance using alternative fuel - Rafiul Alam, Jubayer Abdullah; Abu Talib, Abd Rahim; Mohammed Altarazi, Yazan Sofyan; Yusaf, Talal; Azami, Muhammad Hanafi; Nik Mohd, Nik Ahmad Ridhwan (Aeronautical and Astronautical Society of the Republic of China, 2023)
The usage of fossil fuels is a significant contributor to carbon emissions in the aviation industry. Therefore, it is essential to identify alternative energy sources to power modern aircraft. This paper examines the application of biofuels as aviation fuel, which has a lower lifecycle emission compared to fossil fuels. The chosen biofuel was Palm methyl ester, which was blended with Jet A1 at various volume ratios to determine the optimal blend ratio. The KingTech K180 micro gas turbine engine was used to evaluate the thrust produced for each fuel type at different engine speeds, and the engine pump pulse width was recorded for the corresponding thrust. The results were manually recorded and compared using Python. The study found that the performance remained satisfactory for a blend ratio as high as B50 (50% biodiesel mixed with Jet A1), with maximum thrust comparable to Jet A1. However, B70 and B100 produced significantly less thrust (around 11% and 15% less, respectively). The pump pulse width, which indicates fuel flow, was particularly good for B20, but increased linearly with additional biofuel content.